Challenges and considerations of genetic testing in von Willebrand disease - Omid Seidizadeh; Luciano Baronciani; Flora Peyvandi (Research and Practice in Thrombosis and Haemostasis)
von Willebrand disease (VWD) is the most common inherited bleeding disorder characterized by defects in the quantity or function of the von Willebrand factor (VWF). The diagnosis of VWD is complex, requiring a battery of tests to evaluate the amount, functions, and multimeric structure of the VWF glycoprotein. The diagnosis can also be accomplished or confirmed by sequencing the VWF gene (VWF). Genetic testing of VWF has been around for 4 decades following the cloning of VWF, and nowadays, it has been integrated into the diagnostic panel of VWD. With the introduction of next-generation sequencing, genetic analysis of the VWF has become more practical than it was in the past, when Sanger sequencing was used. A number of laboratories have applied or started to use genetic testing with next-generation sequencing for VWD diagnosis. Considering the increasing application of genetic testing in VWD and the wide availability and decreasing cost of gene sequencing, we sought to discuss the challenges and considerations involved in applying genetic testing to VWD.